α-Synuclein aggregation decreases cortico-amygdala connectivity and impairs social behavior in mice - Wei Zhou; Samuel Daniels; Vijay Singh; Marissa Menard; Martha L. Escobar Galvis; Hong-Yuan Chu (Neurobiology of Disease)
Abnormal accumulation of insoluble α-synuclein (α-Syn) inclusions in neurons, neurites, and glial cells is the defining neuropathology of synucleinopathies, including Parkinson's disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy. Accumulation of α-Syn inclusions in the amygdala has been well-documented in post-mortem studies of PD and DLB brains, as well as preclinical animal models of these conditions. Though α-Syn pathology is closely associated with neurodegeneration, there is a poor correlation between neuronal loss in the amygdala and the clinical features of PD and DLB. Moreover, functional interaction between the cerebral cortex and the amygdala is critical to regulating emotion, motivation, and social behaviors. The cortico-amygdala functional interaction is likely to be disrupted by the development of α-Syn pathology in the brain. Thus, we hypothesize that neuronal α-Syn inclusions disrupt cortical modulation of the amygdala circuits and are sufficient to drive social behavioral deficits. In the present work, we designed a series of longitudinal studies to rigorously measure the time courses of neurodegeneration, functional impairment of cortico-amygdala connectivity, and development of amygdala-dependent social behavioral deficits to test this hypothesis. We injected α-Syn preformed fibrils (PFFs) into the dorsal striatum to induce α-Syn aggregation in the amygdala and the medial prefrontal cortex (mPFC) of C57BL6 mice of both sexes, followed by a detailed analysis of temporal development of α-Syn pathology, synaptic deficits, and neuronal loss in the amygdala, as well as behavioral deficits at 3–12 months post injections. Development of α-Syn inclusions caused losses of cortical axon terminals and cell death in the basolateral amygdala (BLA) at 6- and 12-months post injections, respectively. At a relatively early stage of 3 months post injections, the connection strength of the mPFC-BLA synapse was decreased in PFFs-injection mice compared to controls. Meanwhile, the PFFs-injected mice showed impaired social interaction behavior, which was rescued by chemogenetic stimulation of mPFC-BLA connections. Altogether, we presented a series of evidence to delineate circuit events in the amygdala associated with the accumulation of α-Syn inclusions in the mouse brain, highlighting that functional impairment of the amygdala is sufficient to cause social behavior deficits. The present work further suggests that early circuit modulation could be an effective approach to alleviate symptoms associated with α-Syn pathology, necessitating studies of functional consequences of α-Syn aggregation.